ANALISIS PENGARUH TINGKAT PENDIDIKAN, KESEHATAN, DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP KEMISKINAN DI KABUPATEN GAYO LUES TAHUN 2010 – 2024 - Yessi Tamba; Sri Asmaul Husnah; Asnidar Asnidar; Puti Andiny; Nurlaila Hanum; Safuridar Safuridar (Universitas Veteran Bangun Nusantara, 2025)
Gayo Lues Regency has the second highest poverty rate in Aceh Province. This condition indicates structural problems related to employment, health, and education. This study aims to analyze the influence of open poverty, health levels, and educational attainment on poverty levels in Gayo Lues Regency during the 2010–2024 period. This study uses a quantitative approach utilizing secondary data obtained from the Central Statistics Agency (BPS) of Aceh Province. The analytical methods used include time series analysis and multiple linear regression to identify the relationship and magnitude of influence between variables. The results show that health and open poverty variables have a positive but insignificant influence on poverty levels. Meanwhile, education levels show a significant negative influence on poverty, indicating that improving education plays a significant role in reducing poverty rates. These findings emphasize that poverty alleviation efforts in Gayo Lues Regency need to be directed at improving the quality and access to education and creating productive and sustainable employment opportunities to improve overall community welfare.